2010
DOI: 10.1021/jp910706m
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Viscosity Behavior of Asymmetric Phosphonium Iodides

Abstract: In this work, we report the physicochemical properties of a variety of aliphatic phosphonium iodide (API) salts, including thermal degradation. Also, we compared the conductivity, viscosity, and fragility behavior of APIs to similar molten systems and related these properties to their structure. Our investigation has found that APIs have an intermediate fragility behavior. We plotted the conductivity and viscosity data of APIs according to Walden's rule and found that they can be classified as an associated io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Nutricionalmente es una fruta con alto contenido en agua, carbohidratos, proteínas, bajo contenido en lípidos y otros compuestos (Barreca et al, 2011) y se han identificado otros compuestos con posibles efectos beneficiosos para la salud, como la cherimolina, la cherinonaína, los kauranos, los lignanos, las amidas, las acetogeninas, la lactamamida, las purinas, los esteroides, los alcaloides, la p-quinona, los bencenoides y las poliaminas (Vega-González, 2013). Se utilizan varios ensayos para evaluar si un compuesto puede ejercer un efecto sobre la modulación de eventos bioquímicos relacionados con la carcinogénesis, uno de los cuales es la inhibición de las topoisomerasas (Bertozzi et al, 2014;Ramírez-Mares et al, 2010;Jang et al, 2019). Ensayos basados en modelos de Saccharomyces cerevisiae con una modificación en el gen que codifica la reparación del ADN (Matα ura3-52 leu2 trp1 his7 ade1-2 ISE2 rad52 :: LEU2), permite evaluar extractos y compuestos con potencial actividad antitopoisomerasa (Nitiss, J. L. & Nitiss, K. C. 2001;Nitiss, J.…”
Section: Introductionunclassified
“…Nutricionalmente es una fruta con alto contenido en agua, carbohidratos, proteínas, bajo contenido en lípidos y otros compuestos (Barreca et al, 2011) y se han identificado otros compuestos con posibles efectos beneficiosos para la salud, como la cherimolina, la cherinonaína, los kauranos, los lignanos, las amidas, las acetogeninas, la lactamamida, las purinas, los esteroides, los alcaloides, la p-quinona, los bencenoides y las poliaminas (Vega-González, 2013). Se utilizan varios ensayos para evaluar si un compuesto puede ejercer un efecto sobre la modulación de eventos bioquímicos relacionados con la carcinogénesis, uno de los cuales es la inhibición de las topoisomerasas (Bertozzi et al, 2014;Ramírez-Mares et al, 2010;Jang et al, 2019). Ensayos basados en modelos de Saccharomyces cerevisiae con una modificación en el gen que codifica la reparación del ADN (Matα ura3-52 leu2 trp1 his7 ade1-2 ISE2 rad52 :: LEU2), permite evaluar extractos y compuestos con potencial actividad antitopoisomerasa (Nitiss, J. L. & Nitiss, K. C. 2001;Nitiss, J.…”
Section: Introductionunclassified
“…The Walden plot is the plot of molar conductivity against reciprocal shear viscosity, which is often employed in the analysis of ionic transport of ionic liquids. According to the position on the Walden plot relative to the so-called “ideal line”, which is determined with aqueous KCl solution, ionic liquids are classified into three categories. The first one, “good ionic liquid”, is for ionic liquids near the ideal line.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown, that one way to tackle this problem is the addition of molecular liquids [11–14] . Thereby, water was revealed to be the most promising candidate to optimize the ILs properties in terms of the application as electrolytes by the enhancement of the diffusivity of the ions [12,15–19] . Unfortunately, water has a low electrochemical window of 1.23 V which restricts the applicability of water‐based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 12 , 13 , 14 ] Thereby, water was revealed to be the most promising candidate to optimize the ILs properties in terms of the application as electrolytes by the enhancement of the diffusivity of the ions. [ 12 , 15 , 16 , 17 , 18 , 19 ] Unfortunately, water has a low electrochemical window of 1.23 V which restricts the applicability of water‐based electrolytes. However, it has been shown that the behavior of water differs significantly if the amount of ionic liquid clearly outnumbers the amount of water.…”
Section: Introductionmentioning
confidence: 99%